Do university graduate competences match post-socialist labour market demands:? Evidence from Azerbaijan - Gulsabah Amirova (Deakin University, 2021)
The recruitment and selection process in companies is becoming more complicated as employers place more emphasis on ‘intangible personal qualities’ rather than specialised skills. Employers also require graduates to adapt to the workplace on completion of their education. In particular, following the Bologna Declaration in 1999, the expansion of higher education across Europe has resulted in the questioning of the quality of the graduate labour market. To gain further insight into the mismatch between the employability skills of graduates on the one hand and labour market demands on the other, this paper examines the case of Azerbaijan, a country that is slowly entering the global network. The study synthesised and analysed 24 ‘transferable’ soft skills and competences critical for improved graduate employability, resulting in a  shortlist of the top five competences as ranked by Azerbaijani employers and graduates. More than 2,500 students from six major universities participated in the study which found that there is a huge discrepancy between the skills needed by students and the job market when compared with what is taught at university. Furthermore, it revealed that the absence of these necessary skills is a major factor preventing students from finding jobs.